2015
DOI: 10.1007/978-3-662-46943-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Safety Pharmacology in Drug Discovery and Development

Abstract: Although the basic structure of the gastrointestinal tract (GIT) is similar across species, there are significant differences in the anatomy, physiology, and biochemistry between humans and laboratory animals, which should be taken into account when conducting a gastrointestinal (GI) assessment. Historically, the percentage of cases of drug attrition associated with GI-related adverse effects is small; however, this incidence has increased over the last few years. Drug-related GI effects are very diverse, usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 132 publications
(139 reference statements)
0
12
0
Order By: Relevance
“…While an enteric polymer, such as those tested in the present study, would not be absorbed into the blood, it is well established that within the digestive system, GI reflexes can be modulated through both systemic as well as complex local and regional effects processed entirely within the digestive system itself (e.g., to control secretion and local motility via gastro-colic, entero-gastric, and colono-ilial reflexes) ultimately affecting GI function (Furness et al, 2014 ; Al-Saffar et al, 2015 ). The importance of proper formulation excipient characterization has also been noted specifically in support of small-animal telemetry profiling for cardiovascular safety (Guth, 2007 ) to enable detection of the low-magnitude yet physiologically-relevant effects, and where volume, dose rate, and physicochemical characteristics of the excipient are critical factors impacting hemodynamic responses (Authier et al, 2015 ).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…While an enteric polymer, such as those tested in the present study, would not be absorbed into the blood, it is well established that within the digestive system, GI reflexes can be modulated through both systemic as well as complex local and regional effects processed entirely within the digestive system itself (e.g., to control secretion and local motility via gastro-colic, entero-gastric, and colono-ilial reflexes) ultimately affecting GI function (Furness et al, 2014 ; Al-Saffar et al, 2015 ). The importance of proper formulation excipient characterization has also been noted specifically in support of small-animal telemetry profiling for cardiovascular safety (Guth, 2007 ) to enable detection of the low-magnitude yet physiologically-relevant effects, and where volume, dose rate, and physicochemical characteristics of the excipient are critical factors impacting hemodynamic responses (Authier et al, 2015 ).…”
Section: Introductionmentioning
confidence: 70%
“…Moreover, to protect the Phase I volunteer, in vivo studies are mandated by regulatory authorities in key organ systems, including testing in models to investigate effects on CNS, respiratory, and cardiovascular function (USDHHS, 2001 ). Effects on other organ systems (e.g., gastrointestinal and renal function) are also commonly assessed as part of a comprehensive battery of in vivo safety profiling (Al-Saffar et al, 2015 ; Benjamin et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, Valentin and colleagues observed that most GI AEs are functional toxicities thereby indicating that functional screening assays should be prioritized. 4 Third, strategies for managing GIT in the clinic have exploited dose scheduling, thereby suggesting that kinetic data should be generated, if possible, to inform mathematical modelling and guide discovery of optimized clinical schedules (discussed in Enabling PK-PD and mechanistic mathematical modelling). Selecting assay endpoints that measure GI-specific functions in a non-destructive, re-readable manner will likely enhance predictivity and expand utility.…”
Section: Selecting Assay Endpoints For Di-gitmentioning
confidence: 99%
“…Since GITs are generally nonlife-threatening, the medical response tends to focus on dose reduction and/or palliative co-therapies (e.g., anti-diarrheal). 4,5 Whilst such clinical management strategies avoid drug attrition, symptomatic relief is transient, and the underlying issues are not addressed. Hence, the existing safety assessment paradigm results in (i) drugs advancing into the clinic with GI liabilities, (ii) GI-related limitations on dosing/efficacy persisting throughout the drug life cycle, and (iii) patients bearing the burden of reduced quality of life, reduced drug compliance, and compromised efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation